Incoherent Thomson scattering: future implementation and measurement capabilities on the PANDORA experiment - Tsikata, S.; Maunoury, L.; Ducret, J-E. (Frontiers in Astronomy and Space Sciences, 2022)
The PANDORA (Plasmas for Astrophysics Nuclear Decays Observation and Radiation for Archaeometry) experiment aims to study the β-decay process inside a dense plasma mimicking stellar conditions. An electron cyclotron resonance plasma trap will be built at INFN-LNS in Catania, Italy, for the generation of the desired conditions in the laboratory. This type of non equilibrium dense plasma (reaching densities of up to 10^13 cm−3) is expected to generate electron energy distribution functions with electron energies ranging from from tens of eV up to few MeV. In this work, we describe aspects of a planned implementation of an incoherent Thomson scattering diagnostic for the study of electron properties in the plasma trap of PANDORA. The performance of this high-sensitivity diagnostic, known as THETIS, has been previously validated in measurements across a range of low-density magnetized plasma environments and it is expected to provide access to electron energy information in PANDORA in the range of temperatures from 1 to 10^3 eV. This article will establish the potential of such a diagnostic for future characterization of the electron properties in the PANDORA experiment.